Analysis of Planning Implementation Software Testing using the Equivalence Partitions testing method - Supriyadi, Hari (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to make an analysis of planning the implementation of e-hospital information technology testing: Presentation of Location Information and Scheduling of Hospital Doctors in the City of Bandung. It aims to analyze the extent of the suitability of the application of Black Box testing in minimizing the risk of failure of a system when implemented. Make an analysis of planning the implementation of e-hospital information technology testing. The method used is black box testing as a method of testing the implementation of e-hospital information technology, which is related to providing location information and scheduling of doctors at hospitals in Bandung. As for the steps, among others: determination of test cases for software testing, initialization of standards for input and output grade partitions, testing of the Equivalence Partitions Method, and value of the effectiveness level of the Equivalence Partitions Method. The findings of this study can provide an analysis of the appropriateness of the method used in the process of testing the implementation of information technology in the form of eHospital, which can provide convenience for the general public in the city of Bandung or for migrants or tourists who are on vacation in the city of Bandung in obtaining information on the existence of hospital location and scheduling in the city of Bandung. Further observations are needed in the future to provide information related to the use of software testing methods that can have an impact in the form of minimizing the risk of failure of a system when implemented. This research is expected to be able to provide a reference in carrying out the software testing process, especially the use of testing methods, in essence providing a guarantee and minimizing the risk of failure of an application when it is implemented.